The Effect of Exchange Rate, Inflation and GDP Growth on The Share Price of The Mining Sub-Sector Listed on The Indonesia Stock Exchange - Hilman, Akbar; Damanik, Sabas; Marjohan, Masno (Indonesian Development of Economics and Administration Journal, 2025)
This study aims to analyze the influence of exchange rates, inflation, and Gross Domestic Product (GDP) growth on the share price of the mining sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This study uses a quantitative approach with a multiple linear regression method, where secondary data is taken from the company’s financial statements, Bank Indonesia, and the Central Statistics Agency. The results of the analysis show that the exchange rate has a significant positive influence on stock prices, while inflation has a significant negative influence. In contrast, GDP growth showed a negative but not significant influence on stock prices. Simultaneously, these three variables have a significant influence on the share price of the mining sub-sector. These findings indicate that exchange rate fluctuations can increase the income of export-based companies, while rising inflation tends to suppress corporate profit margins. Although GDP growth has a limited impact, the study emphasizes the importance of considering macroeconomic factors in investment decision-making. This research contributes to the capital market literature and can be a guide for investors to manage their portfolios more effectively.